2012
DOI: 10.3109/00365521.2012.699548
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal transit times and motility in patients with cystic fibrosis

Abstract: In spite of normal contraction patterns, overall passage through the small intestine is significantly delayed in CF patients while upper small intestinal transit may be abnormally fast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
(47 reference statements)
2
28
0
Order By: Relevance
“…A previous magnet based system employing a permanent magnet has been used in several studies of GI motility in health and disease . When magnet tracking was combined with simultaneous capsule endoscopy, it showed that tracking of a magnet, provide reliable information about GE and SITT .…”
Section: Discussionmentioning
confidence: 99%
“…A previous magnet based system employing a permanent magnet has been used in several studies of GI motility in health and disease . When magnet tracking was combined with simultaneous capsule endoscopy, it showed that tracking of a magnet, provide reliable information about GE and SITT .…”
Section: Discussionmentioning
confidence: 99%
“…The same problem has been encountered in studies of adult patients, but the limitations were to some extent avoided by calculating the velocity of the magnetic pill during the first hours after pyloric passage. This approach is not ideal, but has allowed us to identify abnormalities in patients with spinal cord injury,16 systemic sclerosis,15 cystic fibrosis,28 and carcinoid syndrome 17. Compared with gastric emptying and small intestinal transit times, colorectal transit time is usually much longer.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have revealed the prolonged small intestinal transit time in adult and pediatric CF patients with exocrine pancreatic insufficiency compared to healthy controls [77][78][79]. The prolonged small intestinal transit time was not corrected by PERT.…”
Section: Small Intestinal Transit Timementioning
confidence: 88%